Discovery of the Late Jurassic-Early Cretaceous Lamprophyres in Western Songliao Basin of Northeast China and Their Constraint on Regional Lithospheric Evolution - Yu, Taiji; Wang, Pujun; Zhang, Yan; Gao, Youfeng; Chen, Chongyang (Frontiers in Earth Science, 2022)
Contradictory to common concept that the lithosphere in NE China was thinned from Late Jurassic through Early Cretaceous. We discovered, however, a thickening episode in the long-term thinning background. A series of lamprophyre dikes have been recently found in the Tuquan Basin of western Songliao Basin. They were subsequently dated at 156.0 ± 2.3 Ma, 132.9 ± 1.2 Ma, and 126.2 ± 2.5 Ma, respectively, using the zircon U–Pb technique. The lamprophyres are subdivided into Late Jurassic biotite orthoclase lamprophyre (BOL) and Early Cretaceous quartz magnetite lamprophyre (QML).The BOL and QMLs are shoshonite and calc-alkaline in series, characterized by high contents of FeOT, TiO2, MgO, and Mg# values, and are enriched in LREEs and LILEs but depleted in HREEs and HFSEs. They have high ratios of (La/Yb)N, La/Ta, La/Nb, Th/Y, Ba/Nb, Ba/Ta, and Ba/Th, and low ratios of Zr/Ba, La/Sm, and Nb/Zr. These features collectively point to the derivation of the dike magmas from the partial melting of enriched lithospheric mantle that had been previously metasomatized by subduction-related fluids. The BOL has high ratios of Rb/Sr (0.42) and K/Yb*1000 (28.3), and low ratios of Ba/Rb (13.5) and Dy/Yb (2.35), suggesting a magma derivation from high degree partial melting of phlogopite-bearing lherzolite mantle in the spinel–garnet transition zone at a depth about 60 km, the QMLs have low ratios of Rb/Sr (0.02–0.06) and K/Yb*1000 (8.13–19.73), and high ratios of Ba/Rb (17.6–42.6) and Dy/Yb (3.48–4.09), indicating that the magmas were derived by low degree partial melting of lherzolite mantle in the garnet zone at a depth of ca. 85 km, the younger QML (126.2 ± 2.5 Ma) has lower Dy/Yb ratio (3.48–3.92) than that of the older QML (132.9 ± 1.2 Ma) with Dy/Yb ratio of 4.09, implying that the younger magma was produced at a shallower mantle depth (＜ 85 km) than that of the older one. These indicate that in the period of 156–132 Ma, the lithosphere thickened by approximately 25 km at a rate of approximately 1.0 km/Myr. A new geodynamic evolution model of three stages was thus proposed.